PERAN LITERASI KEUANGAN DALAM MENINGKATKAN INKLUSI KEUANGAN BAGI IBU RUMAH TANGGA YANG MENGELOLA UMKM - Risdayanti, Risdayanti; Haedar, Haedar; Syafitri, Azifah (Universitas Bumigora, 2024)
Financial inclusion and financial literacy are two important factors that can improve the economic welfare of society, especially housewives who run micro, small and medium enterprises (MSMEs). This research aims to find out how financial literacy influences the financial inclusion of housewives who run MSMEs. This research uses a qualitative approach with a case study design. Data was collected through in-depth interviews with several housewives involved in MSMEs and analyzed using thematic analysis techniques. Research shows that low financial literacy hinders access to formal financial services. Housewives with high financial literacy tend to have easier access to formal financial products. These results highlight the importance of more formal and structured financial literacy training to increase financial inclusion for housewives who run MSMEs. Therefore, this research makes an important contribution to the development of more effective programs to improve financial literacy.